Affair Caught between Two Worlds: A Transcultural Exploration of the “Asian Lover” in Western Literature and Film - Yi, Kuizi (Transactions on Social Science, Education and Humanities Research, 2024)
Based on L’amant, this paper offers a critical discussion of the representations of the “Asian lover” in contemporary Western film and television works. By focusing on a transcultural exploration of the “Asian lover” that combines close-reading of literary and filmic texts with original archival research in contemporary news reports and government files, this paper examines the ongoing debates surrounding the underlying Western cultural stereotype with the East from a global standpoint.